Réponses

2014-04-09T13:44:00+02:00
Bonjour

(-9)+(-8)-(+7)+(+6)-(+5)+(-4).
-9 -8 -7 +6 -5 -4 = + 6 - 33 = - 27

(-13)+(-57)-(-24)-(-38)-(-12)+(+13)
-13 -57 +24 +38 +12 +13 = + 87 - 70 = +17


Meilleure réponse !
2014-04-09T13:45:52+02:00

(-9)+(-8)-(+7)+(+6)-(+5)+(-4).

= -9 - 8 - 7 + 6 - 5 - 4

= -17 - 7 + 6 - 5 - 4

= -24 + 6 - 5 - 4

= -18 - 5 - 4

= -23 - 4

= -27


 (-13)+(-57)-(-24)-(-38)-(-12)+(+13)

= -13 - 57 + 24 + 38 + 12 + 13

= -70 + 24 + 38 + 12 + 13

= -46 + 38 + 12 + 13

= -8 + 12 + 13

= 4 + 13

= 17

Merci, beaucoupp !!!!...
Je t'en prie :)
Vraiment, c'est super !! :)..